How the mere desire for certainty can lead to a preference for men in authority (particularly among political liberals). Issue 8 (28th August 2021) - Baldner, Conrad; Pierro, Antonio; di Santo, Daniela; Cabras, Cristina
Abstract: Women are harmed by stereotypes about their fit for positions of authority and changing these stereotypes is not a simple task. As stereotypes have strong epistemic properties, individuals with a high need for cognitive closure (NCC; i.e., the desire for epistemic certainty) can be more likely to accept these stereotypes and, consequently, to prefer men in positions of authority. Consistent with the reactive liberal hypothesis, this effect could be actually more visible among individuals with both a high NCC and left‐wing political orientations. We supported these hypotheses in a series of three studies. In Study 1 ( N  = 217), we found that manipulated NCC predicted preference for men in authority through stereotypes of women as not being fit for authority in a measurement‐of‐mediation design. In Study 2 ( N  = 151), we supported this effect in a mediation‐as‐process design. In Study 3 ( N  = 391), we found the indirect NCC effect on preference for men in authority was more visible among political liberals. A major implication of this work is that ways of changing the effect of these stereotypes should take into account the NCC, but particularly among individuals with left‐wing beliefs.